Nature and scope of wellness tourism in Western Australia: the case of Magaret River region - Dawkins, M.; Gaunt, E.; Pforr, Christof (School of Management, University of Southern Australia, 2011)
This paper aims to contribute to a better understanding of the nature and scope of the wellness tourism market in Western Australia. The case study presented here explores the Margaret River region in the south west of Western Australia as one of the state's leading wellness destinations. It is in particular the spectacular natural resources of the region that form the basis of its tourism product offerings, including wellness tourism. With this in mind the paper investigates the relationship between the natural environment and wellness experiences as well as the motivations and profile of wellness tourists to the region.